Strategi Manajemen Usaha Kuliner Melalui Pelatihan Pengolahan Makanan Berbasis Ikan Di Kelurahan Randusari Kecamatan Semarang: Strategi Manajemen Usaha Kuliner Melalui Pelatihan Pengolahan Makanan Berbasis Ikan Di Kelurahan Randusari Kecamatan Semarang - U Yuyun Triastuti yuyun; Nisa’ul Chasanah Idris; Julia Vebrianti (UNUSA Press, 2022)
Randusari Village is part of the Semarang sub-district, the city of Semarang, which is a coastal area. Agrarianly as a producing area of marine fish and brackish water fish. As an effort to utilize fish that can increase family income, namely by playing a culinary business management, through fish-based food processing training. The objectives of the activity are 1) to provide information on culinary business management. 2) developing innovative fish-based food products. The benefits provided are efforts to improve the family economy and information on processed fish innovations that have selling value and nutritional value. The method of activity is lectures and demonstrations of fish-based food processing. The service activities were carried out in the Randusari Village hall, with 30 housewives participating. The results obtained by participants were that 85% received increased information about business planning, business implementation, and culinary business marketing. The demonstration resulted in processing fish into: pindang dumplings, catfish dragon legs, spicy fish bakpia, bandeng zuppa soup, tilapia rolls filled with vegetables, bandeng rolls, catfish satay lilit. The fish-based food products are expected to be marketed at the Tiban market, which is open every Sunday, and is managed by residents. The next hope is that the product can be marketed more broadly, and can add variants of souvenir products in the city of Semarang.